2022
DOI: 10.1021/acs.jafc.2c04770
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-Methoxy-(biphenyl-ethyl)-pyrazole-carboxamides as Novel Succinate Dehydrogenase Inhibitors

Abstract: Succinate dehydrogenase (SDH) inhibitor is one of the research hotspots for the development of fungicides. Herein, we describe the design and synthesis of N-methoxy-(biphenyl-ethyl)-pyrazole-carboxamide derivatives with enhanced fungicidal activity by employing fragment combination strategy. The SDH enzymatic activity was evaluated for 24 title compounds, and compound 7s was identified as the highest activity against porcine SDH with an IC50 value of 0.014 μM, 205-fold greater than that of fluxapyroxad. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…To further enhance the activity of inhibitors, we optimized X 2 on the pyrazole scaffold. In our previous study, we found that replacing hydrogen in the pyrazole ring with fluorine could increase the potency of the compounds. , Therefore, compounds G27 – G42 with a fluorine atom on the pyrazole ring were synthesized. Compared to hydrogen-substituent compounds, these fluorine-substituent compounds displayed remarkable enhanced inhibition potency, with IC 50 values essentially reaching several tens of nanomolar levels, such as compounds G28 (4-Cl, IC 50 = 26.00 nM), G33 (4-Br, IC 50 = 31.00 nM), G34 (4-OCF 3 , IC 50 = 77.00 nM), G35 (4-CF 3 , IC 50 = 48.00 nM), and G40 (2-F-4-Cl, IC 50 = 27.00 nM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further enhance the activity of inhibitors, we optimized X 2 on the pyrazole scaffold. In our previous study, we found that replacing hydrogen in the pyrazole ring with fluorine could increase the potency of the compounds. , Therefore, compounds G27 – G42 with a fluorine atom on the pyrazole ring were synthesized. Compared to hydrogen-substituent compounds, these fluorine-substituent compounds displayed remarkable enhanced inhibition potency, with IC 50 values essentially reaching several tens of nanomolar levels, such as compounds G28 (4-Cl, IC 50 = 26.00 nM), G33 (4-Br, IC 50 = 31.00 nM), G34 (4-OCF 3 , IC 50 = 77.00 nM), G35 (4-CF 3 , IC 50 = 48.00 nM), and G40 (2-F-4-Cl, IC 50 = 27.00 nM).…”
Section: Resultsmentioning
confidence: 99%
“… a Δ G exp = −RT ln IC 50 . b Obtained from ref . c R 2 is the correlation coefficient between Δ G exp and other energy terms. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this point, our continuing efforts were attracted by the discovery of novel antifungal ligands based on coenzyme Q itself (e.g., drimane hydroquinones) as well as the rational design (e.g., aryloxazoline) inspired by coenzyme Q binding pockets. The chemical variation of SDHIs has received increasing attention for the discovery and development of new antifungal leads. , The structural diversity has been significantly advanced owing to the merit of a specially designed scaffold. Our research group has been a contributor in this area since 2016 with aryloxazoline as a special model in view of its chemical and biological insights (Figure A).…”
Section: Introductionmentioning
confidence: 99%
“… In recent years, various effective strategies, such as scaffold hopping, bioisosterism, and pharmacophore-linked fragment virtual screening (PFVS) methods, have been employed to optimize pyrazole-4-carboxamides. These strategies have led to the discovery of many SDHIs with distinct structures. According to the cocrystal structure of SDH from the porcine heart, it was observed that the polar segment could be embedded into the ubiquinone binding site, thus resulting in a higher binding affinity for SDHIs. Consequently, the modification of the pyrazole skeleton in a pyrazole-4-carboxamide structure is a promising tactic for the development of novel SDHI fungicides with a higher activity and broader spectrum. ,, …”
Section: Introductionmentioning
confidence: 99%